The Quality Measures Domain in Nursing Home Compare: Is High Performance Meaningful or Misleading?. (27th April 2021) - Konetzka, R Tamara; Davila, Heather; Brauner, Daniel J; Cursio, John F; Sharma, Hari; Werner, Rachel M; Park, Young Shin; Shippee, Tetyana P
Abstract: Background and Objectives: The reported percent of nursing home residents suffering adverse outcomes decreased dramatically since Nursing Home Compare began reporting them, but the validity of scores is questionable for nursing homes that score well on measures using facility-reported data but poorly on inspections. Our objective was to assess whether nursing homes with these "discordant" scores are meaningfully better than nursing homes that score poorly across domains. Research Design and Methods: We used a convergent mixed-methods design, starting with quantitative analyses of 2012–2016 national data. We conducted in-depth interviews and observations in 12 nursing homes in 2017–2018, focusing on how facilities achieved their Nursing Home Compare ratings. Additional quantitative analyses were conducted in parallel to study performance trajectories over time. Quantitative and qualitative results were interpreted together. Results: Discordant facilities engage in more quality improvement strategies than poor performers, but do not seem to invest in quality improvement in resource-intensive, broad-based ways that would spill over into other domains of quality and change their trajectory of improvement. Instead, they focus on lower-resource improvements related to data quality, staff training, leadership, and communication. In contrast, poor-performing facilities seemed to lack the leadership and continuity of staff required for even these low-resource interventions. Discussion and Implications: High performance on the quality measures using facility-reported data is mostly meaningful rather than misleading to consumers who care about those outcomes, although discordant facilities still have quality deficits. The quality measures domain should continue to have a role in Nursing Home Compare.